2011
DOI: 10.32712/2446-4775.2011.126
|View full text |Cite
|
Sign up to set email alerts
|

Tillandsia usneoides (L.) L. (Bromeliaceae): Aspectos Químicos e Farmacológicos.

Abstract: O presente estudo baseia-se no levantamento de dados da literatura cientifica e convencional, com o objetivo de reunir as informações relevantes à espécie Tillandsia usneoides (Bromeliaceae), relacionadas especificamente ao seu potencial medicinal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Tillandsia usneoides is a strictly epiphyte species found in abundance throughout the study area (Figure 5H). This species has the most extensive Neotropical distribution among Bromeliaceae and has several use potentials, such as air bioindicators (FIGUEIREDO et al, 2004), ornamental potential, and medicinal properties of which were recorded the presence of ascorbic acid, carotenoids, flavonoids, xanthones, coumarins, and tannins (MANETTI et al, 2009;VIEIRA;CAPLAN, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Tillandsia usneoides is a strictly epiphyte species found in abundance throughout the study area (Figure 5H). This species has the most extensive Neotropical distribution among Bromeliaceae and has several use potentials, such as air bioindicators (FIGUEIREDO et al, 2004), ornamental potential, and medicinal properties of which were recorded the presence of ascorbic acid, carotenoids, flavonoids, xanthones, coumarins, and tannins (MANETTI et al, 2009;VIEIRA;CAPLAN, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Being used for a long time in the American continent as medicinal plants, the species of the genus Tillandsia have aroused the interest of researchers who have studied the biological properties of their constituents. These studies have demonstrated the presence of compounds with antiangiogenic, antiviral, antitumor, hypoglycemic, and anticancer activities. Regarding antibacterial activity, it was reported in 1945 that the crude extract of T.…”
Section: Discussionmentioning
confidence: 99%